Enantioselective Synthesis of Spiroindenes by Enol-Directed Rhodium(III)-Catalyzed C–H Functionalization and Spiroannulation - Reddy Chidipudi, Suresh (Angew Chem Int Ed Engl, 2015)
Chiral cyclopentadienyl rhodium complexes promote highly enantioselective enol-directed C(sp(2))-H functionalization and oxidative annulation with alkynes to give spiroindenes containing all-carbon quaternary stereocenters. High selectivity between two possible directing groups, as well as control of the direction of rotation in the isomerization of an O-bound rhodium enolate into the C-bound isomer, appear to be critical for high enantiomeric excesses.